A novel authentication and access control framework in wireless sensor networks - Nouri-Moghaddam, Babak; Naji, Hamid Reza (Journal of Advanced Computer Science & Technology, 2015)
Wireless Sensor Networking continues to evolve as one of the most challenging research areas. Considering the insecure nature of these networks and the fact that sensor nodes are distributed in a hostile environment, having a well-implemented security scheme is absolutely essential. Bearing in mind the important security services like authentication and access control, we have proposed a novel security framework for these networks. The new framework is based on Kerberos authentication and access control system. The Kerberos has been adopted for WSNs by utilizing Bloom Filter data structure and Elliptic Curve cryptography. In the proposed scheme, Bloom Filter data structure is used in a novel way; we have used this data structure to get rid of Public Key’s certificates. By combining Bloom Filter data structure and Elliptic Curve cryptography, we achieved a very light robust security framework that offers Authentication, Access Control, and key sharing services. The analysis results showed that our scheme provides more security services and is more robust in the presence of attacks compared to the previous schemes. In contrast, simulation results indicated that our system had significant improvements over the other schemes in many aspects such as power and time expenditure.